KEBIJAKAN PARKIR KOTA BATAM DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH - riyanda, riko; dompak, timbul (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2017)
The growth rate of motor vehicles in Batam City in recent years runs very rapidly. This levy will increase the original revenue of Batam City, But the implementation of the policy of Bylaw No.1 / 2012 on parking that has been running for three years (2012-2015) does not generate significant revenue on parking charges. The Purpose of this research is how the implementationn of parking management system based on evaluation of the policy of Bylaw No.1 / 2012 on parking Btam City. Data retrieval method is done by observation and documentation. Informant selection technique is done by purposive sampling, technical data analysis is done by data reduction, data presentation and conclusion drawing. The result of the research is that the policy of Batam City Government in increasing its achievement PAD not yet optimal, due to some obstacles such as: parking management system is not feasible, there is no public satisfaction survey index to measure the extent to which the achievement of parking policy in Batam City, Human Power that needs coaching and training. Its solution of Batan City government re-filed Ranpeda about parking with the intention of changing parking rates, changing the system of parking management and service facility improvement